Guía para el desarrollo de la expresión oral a través de la música para niños y niñas de 1ero de básica de la escuela fiscal Quintiliano Sánchez - Ponce Toapanta, Delia Consuelo (2013)
This thesis emphasizes the oral expression development in 5 years old children, which can improve with its nine qualities by the application of musical activities,, thus encouraging a good communication in childhood. The conceptual frame work of this paper is divided into three chapters: The first chapter discusses concepts of oral expression, establishing the importance for effective communication; also we look into developed theories of language acquisition and child characteristics/at 5 to 6 years in the cognitive, language development, motor development, social and emotional. The second chapter is a brief study of music and its elements; we study the respective concepts and the importance of this discipline in auditory development, emotional and cognitive development of children/ as. Furthermore, we examine the language of music and its usefulness in interpreting melodies using musical teaching methods Orff, Dalcroze, Kodály and Willems.